2016
DOI: 10.24036/02016546557-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Agresif Siswa dari Keluarga Broken Home

Abstract: This research is based because of the aggressive behavior shown by the students, especially students who come from a broken home. The purpose of this study is to describe the aggressive behavior that is owned by a student who comes from a broken home in terms of attacking people physically, verbally, and damaging and destroying property and wealth of others. The results of this research shows that in general student’s aggressivebehavior are on average level. Implications of research in guidance and counseling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 1 publication
0
5
0
17
Order By: Relevance
“…bahwa "Broken Home merupakan suatu kondisi keluarga yang tidak harmonis dan orangtua tidak lagi menjadi tauladan yang baik untuk anak-anaknya". Hal yang tidak kalah mengherankan adalah "broken home terjadi apabila struktur keluarga itu tidak utuh lagi, misalnya karena kematian salah satu orang tua atau perceraian, kehidupan keluarga tidak harmonis lagi" (Yunistiati, Djalali, & Farid, 2014).Jadi dapat disimpulkan bahwa broken home adalah suatu keadaan yang tidak menguntungkan di dalam keluarga, seperti perceraian, kematian pasangan, maupun kehidupan di dalam keluarga yang tidak harmonis lagi (Pratama, Syahniar, & Karneli, 2016) Penyebab Broken Home Menurut Sanusi (2006) sebab-sebab timbulnya kondisi keluarga Broken Home yaitu:…”
Section: Broken Homeunclassified
“…bahwa "Broken Home merupakan suatu kondisi keluarga yang tidak harmonis dan orangtua tidak lagi menjadi tauladan yang baik untuk anak-anaknya". Hal yang tidak kalah mengherankan adalah "broken home terjadi apabila struktur keluarga itu tidak utuh lagi, misalnya karena kematian salah satu orang tua atau perceraian, kehidupan keluarga tidak harmonis lagi" (Yunistiati, Djalali, & Farid, 2014).Jadi dapat disimpulkan bahwa broken home adalah suatu keadaan yang tidak menguntungkan di dalam keluarga, seperti perceraian, kematian pasangan, maupun kehidupan di dalam keluarga yang tidak harmonis lagi (Pratama, Syahniar, & Karneli, 2016) Penyebab Broken Home Menurut Sanusi (2006) sebab-sebab timbulnya kondisi keluarga Broken Home yaitu:…”
Section: Broken Homeunclassified
“…The study found that the level of aggressiveness of students is quite high (Aziz & Mangestuti 2006;Diana & Retnowati, 2009;Pratt, Masum, & Khan, 2014;Winarlin, Lasan, and Widada,2016). Syahniar & Karneli (2016) showed aggressive behavior in students that occurred in the city of Padang secondary schools in middle category with a percentage of 46%. The occurrence of aggressiveness must not be separated from some of the factors that affect the tendency of the aggressiveness of the students, among which self-identity, self-control, age, gender, and socioeconomic environment (Santrock, 2003;Kartono, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Based on several studies, there are several factors that cause student aggressiveness such as frustration, leadership and compliance, provocation and temperature (Restu and Yusri, 2013), emotional maturity (Annisavitry, 2017), self control (Auliya and Desi, 2014), gender differences (Aulya, Asmidir and Ifdil, 2016), broken family environment (Pratama, Syahniar and Yeni, 2016), lack of parental attention, poor modeling, and motivation for revenge (Yanizon and Vina, 2019).…”
Section: Introductionmentioning
confidence: 99%